Creativity stimulation by idea generation: a resting-state fmri study on effective connectivity - Abdul Hamid K,; Rahman S,; Osman SS,; Azmi NH,; Surat S,; Ahmad Marzuki M,; Yusoff AN, (Penerbit UKM, 2023)
Studies on creativity have bloomed in the past decade. However, little is known about the effective connectivity (EC) between default-mode network (DMN) regions after creativity stimulation. This study aimed to measure the brain connectivity induced by creativity stimulation and to relate it with creativity score. A total of 50 participants were recruited and assigned to control and experimental groups. The experimental participants underwent a two-day creativity stimulation session. Resting state functional magnetic resonance imaging (rs-fMRI) scans were performed on all participants after the session. The rs-fMRI data were analysed using statistical parametric mapping and spectral dynamic causal modelling. A fully connected model comprising angular gyrus (AG), medial pre-frontal cortex (mPFC) and pre-cuneus (PCU) as regions-of-interest (ROIs) was fitted for every participant’s data. The model underwent Bayesian parameter averaging to determine the average strength of connection between ROIs. There was a significant increase in creativity score for the experimental group in the aspect of fluency (p=0.018) and flexibility (p=0.048) except in originality (p>0.05). No difference in brain activation was observed between groups. All the EC between ROIs in the left and right hemisphere for both groups were significant (P>0.9). Symmetrical EC networks for the experimental group were observed with left hemisphere PCU→PCU, PCU→mPFC and AG→PCU connections which were more significant in the experimental group. These findings suggested that creativity stimulation as short as two days was able to evoke changes in creativity score and network connectivity but insufficient to cause convincing differences in the brain activation.